A systematic review of dropout from organized sport among children and youth - Crane, J.; Temple, V. (European Physical Education Review, 2015)
Leisure constraints theory was used as a framework to systematically review factors associated with dropout of organized sport among children and adolescents. Keyword searches for the population, context and construct of interest (i.e. dropout) identified articles from the entire contents of the following databases: Academic Search Complete, ERIC, MEDLINE, PsycINFO and SPORTDiscus. The initial search yielded 557 studies, and 43 met the selection criteria. Most studies focused solely on adolescents, and 89% of participants were male. Most studies were cross-sectional using quantitative approaches. Almost 30 different sports were included in the reviewed studies; however, the most represented sports were soccer, swimming, gymnastics and basketball. Findings from this review indicated that intrapersonal and interpersonal constraints are more frequently associated with dropping out of sport than structural constraints. Although many discrete factors associated with dropout were identified, five major areas emerged: lack of enjoyment, perceptions of competence, social pressures, competing priorities and physical factors (maturation and injuries). Rarely were the interrelationships between factors or the underlying dimensions of factors examined. Future research would benefit from mixed-methods and prospective approaches. These approaches would allow children and youth to explain how their experience of sport shaped their motives to dropout and allow researchers to probe the extent to which affordances and motives for participation aligned with athletes` reasons for dropping out.